2021
DOI: 10.1139/cjfr-2020-0361
|View full text |Cite|
|
Sign up to set email alerts
|

Soil erodibility in European mountain beech forests

Abstract: Forests in Europe are, at present not endangered by soil erosion, however, this can change with climate change or intensified forest management practices. Using a newly established network of plots in beech forests across Europe, the aims of this study were 1) discrimination of soil properties and erodibility indices in relation to bedrock, 2) determination of geochemical properties and Corg influencing erodibility, and 3) assessment of the effect of soil depth on erodibility indices. Seventy-six soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Dolomite and limestone parent materials cause a neutral to moderately alkaline soil reaction (pH 7-8). According to Kašanin-Grubin et al [52], in the investigated sites, the content of organic matter was higher in soils developed on dolomite parent material and was characterized by a decrease in depth. In this study, rendzina was on average a medium-productive forest soil with a higher productive potential on the dolomite parent material in SL (SI = 20901).…”
Section: Analysis Of Site Productivitymentioning
confidence: 75%
See 1 more Smart Citation
“…Dolomite and limestone parent materials cause a neutral to moderately alkaline soil reaction (pH 7-8). According to Kašanin-Grubin et al [52], in the investigated sites, the content of organic matter was higher in soils developed on dolomite parent material and was characterized by a decrease in depth. In this study, rendzina was on average a medium-productive forest soil with a higher productive potential on the dolomite parent material in SL (SI = 20901).…”
Section: Analysis Of Site Productivitymentioning
confidence: 75%
“…The studied rendzina was classified into two subtypes: leptosol developed on dolomite parent material in samples from SL, and rendzina modal developed on limestone parent material on gentle slopes up to 4° in the CZ and a steep slope up to 32° in BA. The higher content of clay fraction in this type of soil was due to topography, abundant wetting, high precipitation, and low evapotranspiration [52]. Dolomite and limestone parent materials cause a neutral to moderately alkaline soil reaction (pH 7-8).…”
Section: Analysis Of Site Productivitymentioning
confidence: 90%
“…Two papers in this issue are concerned with forest soil properties in pure beech stands across Europe. The paper by Dinca et al (2021) analyzed microbial soil biodiversity and the paper by Kašanin-Grubin et al (2021) assessed the erodibility properties of forest soils on different types of bedrock. Because soil microbiology is crucial for soil system functioning, it is important to analyze it in the context of predicted climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Studying physicochemical forest soil properties is important because even though a well-established root system and closed canopy can prevent soil erosion, this might drastically change under a changing climate. Kašanin-Grubin et al (2021) analyzed 76 soil samples from 20 beech forests developed on five bedrock types for a range of physicochemical properties. The authors found that soil susceptibility to erosion follows the order granite > andesite > sandstone > quartzite > limestone and that deeper soil horizons on granite are more susceptible to erosion than surface horizons are, with the opposite trend found for soils on limestone.…”
Section: Introductionmentioning
confidence: 99%
“…According to FAO (2011), forested areas are basically more sensitive to degradation caused by soil erosion than most agricultural surfaces, meadows and pastures. Kašanin-Grubin et al (2021) pointed out that a dramatic reduction in the resistance of forest soil to erosion due to climate change and forest management can be expected.…”
mentioning
confidence: 99%